Information System Literacy Monitoring Health of Hemodialysis Patients: A Health Education Case Study - Lutfatila Masitoh; Cahya Tri Purnami; Aris Puji Widodo (Yayasan Keluarga Guru Mandiri, 2024)
Limited health literacy is associated with faster kidney damage. Kidney failure patients are exposed to a lot of new information about the disease and its treatment, which often results in ineffective communication between the patient and the provider. Increasing the amount, timing, and individualization of information received has been identified as a priority in hemodialysis treatment at health centers. This literature review aims to determine the literacy of the Hemodialysis Patient Health Monitoring Information System. This research is a scoping review, using 4 databases, namely Google Scholar, Ebsco, Pro Quest, and Science Direct. The stages and flow of research article selection used PRISM Flowchart (Preferred Reporting Items For Systematic review and Meta-Analyses), and to assess the quality of the article, researchers used a checklist from the Joanna Briggs Institute. Two themes and five sub-themes were found among the 8 creening articles, namely: (1) Hemodialysis Perspective; (a) Hemodialysis Patient Perspective, (b) Professional Perspective, (c) Anxiety Level at the Beginning of Hemodialysis Treatment. (2) Monitoring the care of hemodialysis patients; (a) Use of Technology in improving compliance and self-management, (b) Health literacy level of hemodialysis patients. Health literacy technology tools such as hemodialysis patient-specific mobile applications are reliable and well validated. Patients who are aware of and understand their disease have better knowledge for better nutritional diet fulfillment.